1 hét - Császi, Ádám; Tóth, Zoltán Gábor (Hungary : Karakter Film, 2003)
The movie 1 Week presents the days of a young gypsy boy, snatching a short excerpt from each day. On Monday morning, Kristóf talks about his family, on Tuesday he goes to a game room with his friends, and on Wednesday he meets his big time buddy. On Thursday, he is publicly dreaming that he will be a big gun too. On Friday, a nervous monologue on the street, followed by mandatory drinking and doing drugs on Saturday night. On Sunday morning, as he stumbles home drunk, two also drunk hungarian guys catch him and beat him.
Romology Film Collection
Keywords: Fiction films